1985
DOI: 10.1038/ki.1985.154
|View full text |Cite
|
Sign up to set email alerts
|

Tubular action of diuretics: Distal effects on electrolyte transport and acidification

Abstract: We used clearance and free-flow micropuncture techniques to evaluate the influence of several diuretic agents, given both individually and in various combinations, on transport of sodium, potassium, and fluid, and on acidification and ammonium transport, within the distal tubule of the rat kidney. The loop diuretics, furosemide and piretanide, sharply increased fractional delivery of fluid, sodium, and potassium into the distal tubule, and, as a result, sodium reabsorption and potassium secretion were enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
90
0
2

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(104 citation statements)
references
References 32 publications
12
90
0
2
Order By: Relevance
“…Studies in mice lacking either the B1 H + -ATPase subunit (ATP6V1B1) or the alpha subunit of the epithelial Na + channel (ENaC) have shed some light on the importance of the connecting tubule as a major segment (97). Application of loop diuretics increases electrogenic urinary acidification, an effect abolished by inhibitors of ENaC function such as amiloride or triamterene (73). In mice lacking the B1 H + -ATPase subunit, specifically expressed in intercalated cells, urinary pH is more alkaline at baseline and does not acidify upon furosemide application.…”
Section: Various Segments and Cells Along The Collecting Duct Contribmentioning
confidence: 99%
“…Studies in mice lacking either the B1 H + -ATPase subunit (ATP6V1B1) or the alpha subunit of the epithelial Na + channel (ENaC) have shed some light on the importance of the connecting tubule as a major segment (97). Application of loop diuretics increases electrogenic urinary acidification, an effect abolished by inhibitors of ENaC function such as amiloride or triamterene (73). In mice lacking the B1 H + -ATPase subunit, specifically expressed in intercalated cells, urinary pH is more alkaline at baseline and does not acidify upon furosemide application.…”
Section: Various Segments and Cells Along The Collecting Duct Contribmentioning
confidence: 99%
“…However, in rabbits, pentagastrin infusion does not seem to increase plasma vasopressin levels (Unwin, Hanson & Lightman, unpublished observations); although unchanged plasma vasopressin concentrations do not exclude endogenous release (Dixey et al, 1986). Free water clearance can also be affected by altered solute transport in the nephron thick ascending limb: (1) in the absence of changes in vasa recta blood flow, and therefore dissipation of the cortico-medullary solute gradient, inhibition of sodium reabsorption in this segment would impair free water generation, and together with an amiloride or triamterene-like effect on distal tubular sodium reabsorption and potassium secretion, could account for some of the net urinary changes observed (Hropot et al, 1985); (2) increased solute reabsorption in this segment together with increased collecting duct water permeability would be more vasopressin-like, with true urine concentration.…”
Section: Main Effects In Rabbit and Manmentioning
confidence: 99%
“…The combination of thiazides with loop diuretics prevents not only the stimulating effect of luminal Na + concentration on NaCl uptake in the early distal tubule, but the thiazides also inhibit carbonic anhydratase (CA) in the proximal tubule, thereby increasing Na + delivery to the TALH [24,[35][36][37]. This is due to the fact that thiazides retain a sulfamyl side group on the benzene ring characteristic of a CA inhibitor such as acetazolamide [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a previous microperfusion study in rats [35], it was shown that thiazides such as HCT or tizolemide increase distal tubular potassium secretion yielding a higher K + excretion than in controls. Yet these kaliuretic agents failed to enhance distal potassium secretion when given together with furosemide or piretanide.…”
Section: +mentioning
confidence: 99%